Integration Of Salaf And Khalaf Education (A Study in Miftahussudur Campor and Misbahul Ulum Campor - abdulwahab; Mad Sa’i; Riza Hamid (Yayasan Azhar Amanaa Yogyakarta, 2023)
Islamic education in Islamic boarding schools is very interesting to study, because firstly, there are many assumptions about the quality of Islamic education in Islamic boarding schools which state that Islamic boarding schools are old-fashioned Islamic education that is not in harmony with the development of the current modern era, so it is necessary to take strategic and urgent steps in in order to develop Islamic education in Islamic boarding schools, for example by collaborating on traditional Islamic boarding schools with modern Islamic boarding schools, secondly, Islamic boarding schools need to carry out development so that they can meet the expectations of the community, third, in the era of globalization which is marked by advances in science and technology. In writing this article, the author tries to analyze the collaborative implementation of the Salaf Education curriculum at the Miftahussudur Campor and Khalaf Islamic boarding schools at the Misbahul Ulum Campor Islamic Boarding School. From the research that the authors conducted on the implementation of education in the two Islamic boarding schools, in the implementation of Islamic education, there were two things that the authors wrote about in this thesis, namely 1. the implementation was carried out at the Miftahussudur Campor Islamic Boarding School and the Misabahul Ulum Campor Islamic Boarding School with the origin of responding to current developments 2 The results of interviews with Islamic boarding school caretakers who are of concern in the implementation of the collaboration between the two schools. During an interview with the author, he stated that what became the basis and continued survival of Islamic boarding schools in implementing this system were the factors of sincerity and sincerity as well as adequate human resources.This is an open-access article under the license